Relatórios integrados: evidências internacionais da geração de valor para os acionistas - Ferreira, Talieh Shaikhzadeh Vahdat (2019)
Corporate reporting has become an essential element in the capital markets, as it is the means by which companies disclose their value creation process. Integrated reporting is changing the landscape of corporate disclosure, and its key objective is to better address market informational demands. In this sense, different forms of report integration are emerging, among which the integrated report has stood out in the international panorama. In this context, this study aimed to analyze the relationship between the disclosure of integrated reports and value creation to shareholders. For this, in the period between 2011 and 2018 three effects were analyzed: the reduction of information asymmetry, the reduction of stock market synchronicity and the increase in earnings predictability. Additionally, it was analyzed if the adoption of a specific framework for the integration of corporate reports, the format proposed by the IIRC, had more pronounced relationships of these effects. For the analysis, two subsamples were built: 1) with companies that adopted integrated reporting regardless of the format used, with 34.887 observations; 2) with companies that specifically adopted the integrated report framework, with 14.011 observations. The identification of the companies that adopt integrated reporting in the two subsamples relied on GRI and IIRC databases, and the control group were selected for the comparative analysis using the Propensity Score Matching (PSM) technique, based on the nearest-neighbor criterion with replacement, aiming to identify peer companies with similar characteristics to minimize the effects not observed in the studied relationships. The analyzes were based on difference-in-difference methodological design and the estimation models had fixed effect for industry, year and country, with robust errors. The results show that after the adoption of integrated reporting there was an addition of shareholder value from the three analyzed perspectives, an effect that was not observed in the same proportion in the subsample that adopts the integrated report framework specifically, since in this sample only a reduction in the information asymmetry was found. Therefore, to create value to the shareholders it is not necessary to adopt a specific disclosure format, but it is necessary to the implement an informational arrangement that integrated financial and non-financial information. Thus, the adoption of integrated reporting is not limited to a legitimation symbol to the companies’ to the market, since it acts as an instrument that improves the informational quality of the markets, enabling the incorporation of a larger portion of companies’ specific information in stock prices, aiding internal decision in a way that results in more predictable earnings.